Psychological Safety Profile Among Contractor Workers in PT X Bekasi - Maselo Fajar Utama; Yuarini Wahyu Pertiwi; Wahyu Auliazalsini Alurmei (CV. Doki Course and Training, 2026)
Introduction: The construction industry is among the highest-risk sectors in Indonesia, with most occupational accidents rooted in behavioural factors linked to low psychological safety. This study aimed to describe the level of psychological safety among contractor employees at PT X Bekasi and its distribution across seven dimensions and demographic characteristics. Method: A quantitative descriptive approach was employed with 100 respondents selected via simple random sampling from a population of 300 workers. Measurement utilised the Psychological Safety Scale (Edmondson, 1999) adapted into Indonesian (7 items; Cronbach's Alpha = 0.727). Data were analysed through descriptive statistics, three-tier categorisation, difference tests, and Chi-Square tests using JASP. Results: Most respondents (56%) exhibited moderate psychological safety, followed by high (42%) and low (2%) categories. At the dimensional level, all dimensions tended to be high, with comfort in seeking help (66%) and social support (65%) ranking highest, while the safety to voice opinions was comparatively weakest. Chi-Square analysis revealed significant differences by educational level (p = 0.012) and job position (p = 0.001). Discussion: Findings indicate that the foundation of psychological safety has been established yet remains suboptimal. Psychological safety is shaped more by work experience, social relationships, and work context than by individual characteristics; thus, strengthening open communication culture and supportive leadership are prioritised as intervention targets.